The effect of outdoor air and indoor human activity on mass concentrations of PM(10), PM(2.5), and PM(1) in a classroom - Branis, Martin; Rezácová, Pavla; Domasová, Markéta (Environmental research, 2005)
The 12-h mass concentration of PM(10), PM(2.5), and PM(1) was measured in a lecturing room by means of three co-located Harvard impactors. The filters were changed at 8 AM and at 8 PM to cover the periods of presence and absence of students. Concentrations were assessed by gravimetry. Ambient PM(10) data were available for corresponding 12-h intervals from the nearest state air-quality-monitoring network station. The data were pooled into four periods according to the presence and absence of students-Monday-Thursday day (workday daytime), Monday-Thursday night (workday night), Friday-Sunday day (weekend daytime), and Friday-Sunday night (weekend night). Average indoor workday daytime concentrations were 42.3, 21.9 and 13.7 microgm(-3), workday night were 20.9, 19.1 and 15.2 microgm(-3), weekend daytime were 21.9, 18.1 and 11.4 microgm(-3), and weekend night were 24.5, 21.3, and 15.6 microgm(-3) for PM(10), PM(2.5), and PM(1), respectively. The highest 12-h mean, median, and maximum (42.3, 43.0, and 76.2 microgm(-3), respectively) indoor concentrations were recorded on workdays during the daytime for PM(10). The statistically significant (r=0.68,P<0.0009) correlation between the number of students per hour per day and the indoor coarse fraction calculated as PM(10--2.5) during daytime on workdays indicates that the presence of people is an important source of coarse particles indoor. On workdays, the daytime PM(10) indoor/outdoor ratio was positively associated (r=0.93) with an increasing indoor coarse fraction (PM(10--2.5)), also indicating that an important portion of indoor PM(10) had its source inside the classroom. With the exception of the calculated coarse fraction (PM(10--2.5)), all of the measured indoor particulate matter fractions were significantly highly correlated with outdoor PM(10) and negatively correlated with wind velocity, showing that outdoor levels of particles influence their indoor concentrations.
Keywords: Air Pollution, Indoor; velikost částic; Cities; vítr; Humidity; monitorování životního prostředí; Particle Size; velkoměsta; vlhkost; časové faktory; Time Factors; lidé; znečištění vzduchu ve vnitřním prostředí; prach; Air Pollutants; Czech Republic; Dust; Environmental Monitoring; Česká republika; Wind; Universities; látky znečišťující vzduch; univerzity; Humans